Review of factors inhibiting outpatient registration services at Ernaldi Bahar Hospital, South Sumatra Province - Limisran, Limisran; Erni juwita; Fina Octa Wijaya (Jurnal EduHealth, 2024)
The outpatient registration place (TPPRJ) or better known as the registration place, is the service provider that the patient or their family first receives so that the quality of service will be assessed here. In the outpatient registration process at the outpatient registration center (TPPRJ), there are several inhibiting factors that disrupt services. The aim of this research is to determine the factors that hinder outpatient registration services. Based on a preliminary survey, there were several obstacles experienced during the registration process which took place at the outpatient registration site (TPPRJ). This research design uses a descriptive method with a qualitative approach. Researchers use subjects as populations and objects as samples. Data collection methods are observation, interviews and documentation. In the research, several things were found, such as factors that hinder outpatient registration services which have an impact on waiting time (response time), and the efforts of officers to overcome obstacles that are inhibiting factors in outpatient registration. It can be concluded that problems in hospitals are caused by the internet sometimes not being connected properly, power outages which force services to stop temporarily, patients being less careful in paying attention to the validity period of referrals. Suggestions from the research results obtained are for officers to improve good communication between officers. with patients, as well as officers and officers, to emphasize the occurrence of obstacles to patient registration services.